The Dynamics of Provincial Growth in China : A Nonparametric Approach - Unel, Bulent (IMF Working Papers; Working Paper, 2006)
China's growth record since the start of its economic reforms in 1978 has been extraordinary. Yet, this impressive performance has been associated with an increasing regional income disparity. We use a recently developed nonparametric approach to analyze the variation in labor productivity growth across China's provinces. This approach imposes less structure on the data than the standard growth accounting framework and allows for a breakdown of labor productivity into capital deepening, efficiency gains, and technological progress. Like other studies before us, we do not find strong evidence of convergence in labor productivity across China's provinces during 1978-98. However, our results show that provinces converged in efficiency levels, while they diverged in capital deepening and technological progress.